69 Are prophylactic hemostatic clips in post-polypectomy overused?. (4th December 2019) - Rhainds, Marc; Bussières, Martin; Asselin, Geneviève; Nourissat, Alice
Abstract : Delayed post-polypectomy bleeding (PPB) is the most common complication in colorectal polypectomy and usually controlled endoscopically in most patient. However, it may be more serious and result in hospitalization, blood transfusion, repeat colonoscopy or surgery. Although prophylactic clipping was introduced to prevent delayed PPB, their use after polypectomy remains controversial. Following a recent increasing use of clips at the CHU de Québec-Université Laval (hereafter «CHU de Québec»), a health technology assessment project was carried on to evaluate the relevance of clipping after polypectomy. Literature searches were conducted in several indexed databases and grey literature from 2008 to 2019. Data on hemostatic clips utilization to prevent delayed PPB following colorectal polypectomy were retrieved. Systematic reviews (SRs), clinical practice guidelines (CPGs) and primary studies were included. Two reviewers independently performed selection, quality assessment and data extraction. A web-based survey to document Québec gastroenterologists practice was completed during autumn 2018. Electronic Patient Record (EPR) analysis were performed to review local use of colorectal clips between August and November 2018. Evidence-based review and local perspective was shared with an interdisciplinary group of local medical experts and hospital managers. According to CPGs (n=2), routine endoscopic clip closure to prevent delayed bleeding for non-pedunculated polyps is not recommended. Results from two SRs suggest that prophylactic clipping did not decrease the occurrence of delayed PPB after colorectal endoscopic resection. Authors of SRs and CPGs suggest to use clips in patients with high risk of bleeding or large lesions. Six randomized control studies (RCT) and four observational retrospective studies (OS) were analysed. Subgroups analysis results (2 RCT, 2 OS) by type of colorectal polyps suggest a significant reduction in PPB with clipping for non-pedunculated polyps (≥ 20 mm) only. Except for frequent devices malfunctions causing mostly no harm to patients, few other adverse events attributable to hemostatic clipping were reported. A survey of gastroenterologists (n=30) revealed that 53% did not use prophylactic clipping after polypectomy for lack of evidence supporting this practice. Among those using hemostatic clips (n=14), all indicated not using them for polyps < 10 mm. The local context from EPR analysis showed that 52% of polyps for which clinicians used clips were inferior to 10 mm. The evidence suggest that prophylactic clipping could be effective to reduce PPB in case of large non-pedunculated polyps only (≥ 20 mm). However, although clinicians stated not using clips for small polyps (<10 mm), local data shows medical practice need to be realign in accordance with the available evidence.